ANALISIS KEBIJAKAN DIVIDEN DAN PEMBELIAN KEMBALI SAHAM SEBAGAI STRATEGI MENINGKATKAN NILAI PERUSAHAAN DI TENGAH VOLATILITAS PASAR - Listiarini, Listiarini; M. Zhafif Nata Nagara (Jurnal Riset Multidisiplin Edukasi, 2025)
This study examines how dividend policy and share repurchase initiatives are used by companies as strategic tools to maintain and enhance firm value during periods of market volatility. Rather than focusing on empirical testing, this review collects and interprets findings from recent academic studies, financial reports, and market analyses to understand how payout decisions influence investor reactions and long-term valuation. The discussion highlights that companies often rely on dividends to communicate consistency and financial stability, especially when uncertainty in the market increases. At the same time, share repurchases are frequently chosen because they offer greater flexibility; firms can adjust the intensity of buybacks according to their liquidity conditions and market circumstances. Several studies also indicate that repurchases may help correct undervaluation and reduce information gaps between managers and investors. Although the two strategies operate differently, many researchers argue that using them together can create a more balanced approach to managing investor expectations. This paper emphasizes that the effectiveness of each policy depends on the company’s financial position, risk profile, and governance quality. The insights presented here provide a broader understanding of payout decisions and may serve as a reference for future research that explores how firms can navigate unstable market conditions while maintaining sustainable value creation.